Rethinking School Feeding Social Safety Nets, Child Development, and the Education Sector - Bundy, Donald; Burbano, Carmen; Grosh, Margaret; Gelli, Aulo; Jukes, Matthew; Drake, Lesley (World Bank, 2012)
This review highlights three main findings. First, school feeding programs in low-income countries exhibit large variation in cost, with concomitant opportunities for cost containment. Second, as countries get richer, school feeding costs become a much smaller proportion of the investment in education. For example, in Zambia the cost of school feeding is about 50 percent of annual per capita costs for primary education; in Ireland it is only 10 percent. Further analysis is required to define these relationships, but supporting countries to maintain an investment in school feeding through this transition may emerge as a key role for development partners. Third, the main preconditions for the transition to sustainable national programs are mainstreaming school feeding in national policies and plans, especially education sector plans; identifying national sources of financing; and expanding national implementation capacity. Mainstreaming a development policy for school feeding into national education sector plans offers the added advantage of aligning support for school feeding with the processes already established to harmonize development partner support for the education for all-fast track initiative.